A bandwidth-efficient CMOS operational amplifier for low-voltage applications - Ding, Jeng Chung (2008)
This project is exploited to design and implement a bandwidth-efficient operational amplifier, with particular emphasis on low-voltage operation. This work covers the analysis, design and simulations of a new high-performance CMOS operational amplifier.